Social Protest, Constructive Criticism and Unionism: The Tripartite Derivatives for State Management in Nigeria: Array - Omamuyovwi, Afonughe Irikefe (Journal of Danubian Studies and Research, 2020)
This paper examined the trine cord nature of social protest, constructive criticism and unionism to governance in Nigeria as stated in Article 11 of the African Charter on Human and People’s right and other international laws. As a qualitative research it relied heavily on secondary source of information such as newspapers, journals and published works which are content analyze to befit the work. The paper adopted the system theory as a frame work of analysis because of its emphasis on input, output, feedback mechanism and stability of the status quo. After verification it is safe to mention that the formative life cycle of Nigeria as a country began from social protest, criticism and domestic allied group. This underscores the pivotal place of these trine cords in the independence of Nigeria as well as its political attainment. However, it is of no news that several military and democratic regimes in Nigeria have not come to terms with any act of obvious opposition due to their ever corrosive reactions. Thus, the work made series of recommendations such as follows: Government should consciously accept the place of pluralism in a democratic system of government, the business of government should be run with openness instead of opacity. More so, government as an institution should appreciate the place of dynamism as nothing is constant and so they should be open to criticism and accept the need for a change when necessary. Wilder consultation through bottom up approach should be a consistent order so as to continuously reflect the wishes of the people. In order words the public choice approach to policy formulation should never be negated. This will reduce the level of social clamour in a political system.